Academic Task Overload and its Influence on the Productivity and Mental Health of Information Technology Students: A Basis for Curriculum Review (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Academic task overload has become a growing concern among university students, particularly in demanding programs such as Information Technology, due to its potential effects on students’ productivity and mental health. This study aimed to determine the influence of academic task overload on the productivity and mental health of Information Technology students at Quezon City University and to provide a basis for curriculum review. Specifically, the study examined the respondents’ demographic profile, the level of academic task overload, productivity, and mental health, as well as the significant relationships and differences among the identified variables. The study employed a quantitative correlational research design utilizing a structured survey questionnaire distributed to 400 Information Technology students from first year to fourth year levels. The gathered data were analyzed using descriptive statistics, Pearson Product-Moment Correlation Coefficient, Independent Samples t-test, and One-Way Analysis of Variance (ANOVA). The findings revealed that the respondents experienced a high level of academic task overload, maintained a high level of academic productivity, and commonly experienced mental health concerns associated with academic demands. The study further revealed significant relationships between academic task overload and both productivity and mental health. In addition, significant differences were identified in selected variables when respondents were grouped according to gender, year level, and primary study habits. Overall, the study highlights the importance of managing academic workload and promoting strategies that support students’ productivity and mental well-being within Information Technology education programs.